INFLUENCE OF SUGARCANE CULTIVATION ON SOIL LOSSES BY WATER EROSION IN INCEPTSOLS IN SAO PAULO STATE - Correa, Edvania Aparecida; Moraes, Isabel Cristina; Lupinacci, Cenira Maria [UNESP]; Ferreira Pinto, Sergio dos Anjos [UNESP] (Uniao Geomorfologia Brasileira, 2018)
Considering the importance of Sao Paulo state in the sugarcane production in Brazil, the objective of this work was to evaluate the interference of this cultivation in soil losses by water erosion in Inceptisols with sandy loam texture from the east of Sao Paulo. To quantify the soil losses it was used four monitoring plots, located in the catchment area of the Monjolo Grande creek, belonging to the Corumbatai river basin. To evaluate the vegetative vigor, values of NDVI were obtained in different stages of sugarcane growth and in plots lacking vegetation cover. During the experimental year Sep/2013 to Sep/2014, the erosivity of 4546.8 MJ/ha/year was responsible for total losses of 74.03 and 206.53 t ha(-1) year(-1) in the two plots of exposed soil, and 49.04 and 84.85 t ha(-1) year(-1) in the two sugarcane plots. The coincidence between the rainy periods and the absence of cover in the off-season and in the initial stages of plating aggravate the erosive processes. The highest levels of fine sand and declining higher than 12% indicated greater erosive susceptibility. The conditions of water limitation and nutritional deficiency compromised the vegetative development, reducing soil protection. The results confirm the need to adapt land use practices in the study area.
Keywords: Sandy soils; Quantification of soil loss; NDVI